2022
DOI: 10.1016/j.omtn.2021.11.005
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA Chordc1 protects mice from abdominal aortic aneurysm by contributing to the phenotype and growth of vascular smooth muscle cells

Abstract: Circular RNAs (circRNAs) have important potential in modulating vascular smooth muscle cell (VSMC) activity, but their roles in abdominal aortic aneurysm (AAA) are unknown. We performed in situ hybridization and immunohistochemistry and determined that circChordc1 (cysteine and histidine-rich domain containing 1) was markedly downregulated in aneurysm tissue compared with normal arteries. A gene gain and loss strategy was used to confirm that circChordc1 transformed VSMCs into a contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…CircChordc1 was found to be significantly deregulated in aneurysmal tissue compared to healthy arteries, and it was capable of converting VSMCs to a contractile phenotype and improving their growth by triggering waveform protein degeneration and boosting the GSK3/-catenin pathway, which inhibited aneurysm formation and minimized the chances of fracture in angiotensin II and CaCl2-induced AAA mouse models [ 72 ].…”
Section: Cardiovascular Diseases Associated With Vsmcs Phenotypic Swi...mentioning
confidence: 99%
“…CircChordc1 was found to be significantly deregulated in aneurysmal tissue compared to healthy arteries, and it was capable of converting VSMCs to a contractile phenotype and improving their growth by triggering waveform protein degeneration and boosting the GSK3/-catenin pathway, which inhibited aneurysm formation and minimized the chances of fracture in angiotensin II and CaCl2-induced AAA mouse models [ 72 ].…”
Section: Cardiovascular Diseases Associated With Vsmcs Phenotypic Swi...mentioning
confidence: 99%
“…Arencibia et al showed that lncRNAs regulate VSMCPS and participate in the pathological process of in-stent stenosis ( Arencibia et al, 2022 ). Additionally, He et al showed that circChordc1 could suppress vascular remodeling and reverse pathological aortic aneurysm progression through optimized VSMCPS and improved their growth ( He et al, 2022 ). However, hitherto, no effective drugs targeting these non-coding RNA are available for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…We next explored the relationship between ANXA2 and β-catenin pathway. A previous report showed that ANXA2 interacts with GSK3β in other organ (30). Hence, we tested whether ANXA2 could bind to GSK3β in renal tubular cells.…”
Section: Anxa2 Promotes Lysosomal Functions Through βCatenin/tcf4 Sig...mentioning
confidence: 95%